How effective is the Taylor rule? Some insights from the time-frequency domain - Patrick M. Crowley; David Hudgins (Bank of Finland, 2020)
When the central bank sets monetary policy according to a conventional or modified Taylor rule (which is known as the Taylor Principle), does this deliver the best outcome for the mac-roeconomy as a whole? This question is addressed by extending the wavelet-based control (WBC) model of Crowley and Hudgins (2015) to evaluate macroeconomic performance when the central bank sets interest rates based on a conventional or modified Taylor rule (TR). We compare the simulated performance of jointly optimal fiscal and monetary policy under an unrestricted baseline model with performance under the TR. We simulate the model un-der relatively small and large weighting of the output gap in the TR specification, and for both low and high inflation environments. The results show that the macroeconomic outcome de-pends on whether the conventional or modified Taylor rule is used, and whether the central bank is operating in a low or high inflation environment.
urn:nbn:fi:bof-202002192000
Keywords: C61; C63; C88; E52; E61; F47; 330; Discrete Wavelet Analysis; Monetary Policy; Optimal Control